Nilai Transaksi Internet Banking dan Rata-Rata DPK Rumah Tangga di Indonesia: Analisis Jangka Panjang dan Jangka Pendek - Ahmad Ilham Abtasuni; Muhamad Abdul Jabbar; Fakhry Ilyas (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This This study analyzes the effect of banking digitalization on household savings in Indonesia. Digitalization is measured through the value of internet banking transactions, taking into account economic growth, policy interest rates, and consumer confidence indices as control variables. This study aims to analyze the effect of banking digitalization, proxied by the value of internet banking transactions, on household savings in Indonesia. The method used is a quantitative approach with an Autoregressive Distributed Lag (ARDL) model using quarterly data from the 2015–2024 period. The results show a long-term relationship between digitalization and household savings. Internet banking transaction values have a negative effect on the average household Third Party Funds (DPK), while economic growth and policy interest rates have a significant positive effect. Meanwhile, consumer confidence has a negative effect because increased economic optimism encourages consumption. These findings indicate that banking digitalization accelerates transaction efficiency but can suppress the accumulation of conventional savings. Therefore, banking digital strategies need to be directed to maintain a balance between technological innovation and the function of financial intermediation.